Fuzzy batch controller for granular materials; MATEC Web of Conferences; Vol. 143 : Youth, Science, Solutions: Ideas and Prospects (YSSIP-2017) - Zamyatin N. V. Nikolay Vladimirovich; Smirnov G. V. Gennady Vasiljevich; Fedorchuk Yu. M. Yuri Mitrofanovich; Rusina O. N. Olga Nikolaevna (2018, 2018)
Title screen